Aspek Fisik Dan Psikis Serta Kehidupan Sosial Pada Puisi “Sundari” Karya Tegar Prasetyo : Kajian Feminisme - Tegar Prasetyo (Universitas Wijaya Kusuma Surabaya, 2022)
AbstractPoetry is a literary work that contains expressions of feelings, experiences, imagination, and the results of human thought that have aesthetic value which is presented using emotional language and poured into written form. The purpose of this study is to describe the physical, psychological, and social aspects of the poem